Natural convection flow near a vertical plate that applies a shear stress to a viscous fluid. - Qammar Rubbab; Dumitru Vieru; Corina Fetecau; Constantin Fetecau (PLoS ONE, 2013)
The unsteady natural convection flow of an incompressible viscous fluid near a vertical plate that applies an arbitrary shear stress to the fluid is studied using the Laplace transform technique. The fluid flow is due to both the shear and the heating of the plate. Closed-form expressions for velocity and temperature are established under the usual Boussinesq approximation. For illustration purposes, two special cases are considered and the influence of pertinent parameters on the fluid motion is graphically underlined. The required time to reach the steady state in the case of oscillating shear stresses on the boundary is also determined.